Protection of personal data under martial law in Ukraine (Law and Safety, 2023)
The article is devoted to the issue of personal data protection under martial law in Ukraine. A detailed study of this issue has been carried out, aspects of the regulatory environment and levels of personal data protection in such difficult conditions have been considered.In the context of martial law, the violation of the personal data confidentiality may pose serious threats. It has been highlighted that the disclosure of such data can lead to a risk to the personal safety of people, including those involved in the conflict. This can become the basis for blackmail and manipulation, which negatively affects the situation of individuals and the overall situation.The recommendations aimed at preventing such threats and improving the level of personal data protection during martial law have been provided. Particular attention has been paid to the need to develop and implement specialised legal acts that would regulate the protection of personal data in such emergency situations. The possibilities of using modern technologies, in particular data encryption and multi-level authentication, to enhance the security and confidentiality of personal data have also been considered.Implementation of effective personal data protection measures during martial law is an important task to ensure the security and privacy of people. Compliance with regulatory requirements, development of data protection technologies and raising awareness of this issue among the population can help reduce risks and maintain the confidentiality of personal data even in the context of a military conflict.The conclusions presented in this article can be a valuable source of information for legislators and information security professionals dealing with personal data protection under martial law. The results of the study may contribute to the development and implementation of effective data protection strategies aimed at ensuring the security and privacy of participants to the conflict and citizens in general. Significant aspects of the problem of personal data protection under martial law have been considered and recommendations for improving the situation in this area have been provided.
Keywords: martial law; personal data protection; cybersecurity; legislation; privacy; state security; encryption; access control.